Effect of mechanical vibration applied in the direction of the resultant muscle forces` vector addition on maximal isometric force production in judo athletes - Oliveira, M.; Teobaldo, B.; Albuquerque, M.; Prado, L.; Szmuchrowski, L.; Andrade, S.; Drummond, M.; Pena, E.; Goncalves, R.; Campos, D.; Pena, B. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background and Study Aim: Judo can be characterised as an intermittent and high-intensity sport, which demands motor actions like pushing, pulling, dominating and throwing the opponent. The combat requires a combination of different expressions of muscle strength, such as maximal and submaximal strength efforts in the upper limbs during the gripping combat (kumi-kata), to control the distance between the opponent and preparation of the throws. The aim of the present study was the effects of mechanical vibrations applied in the direction of the resultant muscle forces produced on the maximal isometric strength of the upper limbs muscles in judo athletes.